2017
DOI: 10.1002/cctc.201701140
|View full text |Cite
|
Sign up to set email alerts
|

Boron and Boron‐Containing Catalysts for the Oxidative Dehydrogenation of Propane

Abstract: The front cover artwork for Issue 19/2017 is provided by the Hermans Laboratory at UW-Madison (USA). The image shows the Swedish Chef who, being offered the scientific freedom to explore new recipes, discovered that boron is the most efficient catalystf or the oxidative upgrading of natural gas-derived alkanest oh ighly-desired olefins. It is ag ood remindert o the scientificcommunity that despited ecades of systematic research on ODH, serendipitous breakthroughsare still possible and can lead to new insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 20 publications
14
121
0
Order By: Relevance
“…Because other boron-containing catalysts (B 4 C , WB, NiB) with oxidizeds urface boron speciesc atalyze the ODH of alkanes with the same selectivity as hBN, [25] we envision that these materials will follow the same trends in reactivity observed for hBN when evaluated for their performance in oxidative cracking. Therefore, boron-containing materials are ahighlyversatile platform for selective hydrocarbon oxidations, and new materials can be engineered to meet the needs of new oxidative technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because other boron-containing catalysts (B 4 C , WB, NiB) with oxidizeds urface boron speciesc atalyze the ODH of alkanes with the same selectivity as hBN, [25] we envision that these materials will follow the same trends in reactivity observed for hBN when evaluated for their performance in oxidative cracking. Therefore, boron-containing materials are ahighlyversatile platform for selective hydrocarbon oxidations, and new materials can be engineered to meet the needs of new oxidative technology.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, our group has shown that hexagonal boron nitride (hBN), boron nitride nanotubes (BNNTs), and other boron‐containing catalysts exhibit high selectivity in the oxidative dehydrogenation (ODH) of propane, n ‐butane, and isobutane . In these studies, a variety of spectroscopic techniques such as Raman, IR, and X‐ray photoelectron spectroscopy (XPS) revealed that after exposure to reaction conditions, these boron‐containing materials become functionalized with oxygen on their surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ha bstraction from propane by > BOC leads to the formation of BOH surface species that have been verified experimentally in previous investigations. [1,8,26] These sites, however, are expected to be fairly unreactive and, as such, we investigated active-site regeneration. Starting from the experimental observation that water enhances the observed reaction rate at all studied reaction conditions,w ea ssessed the possibility of water enabling active-site regeneration.…”
Section: Methodsmentioning
confidence: 99%
“…[4] In fact, it seems good ODH performance can be obtained with any material provided it contains boron. [5,6] Despite the high temperatures required, usually in excess of 500 • C, surprisingly little attention has been paid to gas-phase kinetics. Blank experiments with SiO 2 instead of BN in the reactor show almost no conversion.…”
Section: Introductionmentioning
confidence: 99%